FORMATION OF A PASSENGER TRANSPORTATION STRATEGY ON THE BASIS OF CUSTOMER-ORIENTATION AND DIGITALIZATION OF THE TRANSPORT INDUSTRY OF UKRAINE - MEDYNA, Andrii; USTILOVSKA, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines issues related to the structure and importance of the transport system of Ukraine. An analysis of the logistics efficiency index was carried out, which allows to form promising vectors of the industry’s development by grouping according to country indicators. According to the results of the conducted cluster analysis, four groups of European countries were formed, according to which it was determined that the transport industry of Ukraine and the analyzed European countries has a certain similarity, which is caused, first of all, by a good geographical location and the identity of the characteristics of the transport infrastructure. It has been established that transportation is extremely important not only at the level of the country, but also at the level of an individual citizen, so passenger transportation is given special attention. For the analysis of passenger transportation, the municipal enterprise "Kyivpastrans" was chosen, which is one of the largest in Kyiv and Ukraine, the main activity of which is the transportation of passengers in the city of Kyiv. Economic and mathematical modeling methods were used to determine the impact and importance of various indicators on the net income from the provision of services of KP "Kyivpastrans" (resulting indicator). It has been proven that the model is statistically reliable and can be used to analyze the influence of factors on the efficiency of municipal transport in the city of Kyiv. The analysis of the linear regression model showed that the number of passengers and the cost of vehicles have the greatest influence on the net income from the sale of products. Other factors (investments in the renewal of vehicles and profitability of passenger transport) do not have sufficient influence, which is confirmed by means of economic-mathematical modeling methods. A matrix of development strategies for improving the quality of transport services has been built, which is based on the direct interdependence of the level of digitalization of the transport enterprise management system and the assessment of the level of customer satisfaction, created on the basis of a questionnaire conducted among Kyiv residents.